A Methodology to Determine the Sensitivity of Horizontal Equity Measures to Detect Changes in Distributional Equity - Sidney Castle (Educational Considerations, 1992)
With the courts being presented with a new round of challenges to state public educational finance systems it is important, especially in view of continued poor state fiscal conditions, that researchers are able to more accurately identify the extent to which past and contemplated new school finance reform efforts affect educational resource distributional equity.